EKONOMI PERBATASAN INDONESIA: ANTARA KETERGANTUNGAN, KERJA SAMA LINTAS NEGARA, DAN TANTANGAN PEMBANGUNAN - Melyana R Pugu (Adiba Aisha Amira, 2026)
This study discusses Indonesia’s border economy as a strategic space shaped by economic dependence, cross-border cooperation, and development challenges. Border areas are not only territorial boundaries of state sovereignty but also dynamic zones of social, cultural, and economic interaction between local communities and neighboring countries. Using a library research method, this study analyzes relevant literature, including academic journals, policy documents, and institutional reports, on border economies, cross-border trade, regional cooperation, and local development. The findings show that economic dependence in Indonesia’s border areas is mainly caused by geographical proximity to neighboring countries, limited domestic infrastructure, weak distribution networks, price differences, and easier access to external markets. Cross-border trade, both formal and informal, plays an important role in supporting local livelihoods, but it also raises governance issues, such as weak monitoring, unrecorded transactions, and potential smuggling. Furthermore, cross-border cooperation is identified as a strategic instrument to transform dependency into productive interdependence. However, this transformation requires stronger infrastructure, integrated governance, local economic empowerment, and active participation from the central government, local authorities, business actors, and border communities. The study concludes that Indonesia’s border economy should not be viewed merely as a peripheral or security-based issue, but as a potential regional growth center. Therefore, development strategies must combine protection of sovereignty, improvement of welfare, local competitiveness, and sustainable cross-border cooperation.